Antecedents of work satisfaction among employees with special needs child - Abdul Rahman, Segufta Yasmi; Abu Samah, Bahaman; Mohd Rasdi, Roziah; Sabri, Mohamad Fazli (Faculty of Educational Studies, Universiti Putra Malaysia, 2019)
Issues related to employees with special needs child greatly affects the work satisfaction. Employees who, faced with this issues have problems related to ethical, financial, health, quit the job and task delayed, which are lead to a decreasing of employees work satisfaction. From the literature review that conducted by researcher, there is a lack of study of employees with special need child in a quantitative method and in work satisfaction area specifically. Work Satisfaction can defined as a measure of employee’s contentedness with their job, whether or not they like the job or individual aspects or facets of jobs, such as the nature of work or supervision. and they can balance their work life and personal life. This has happened when the employees give full commitment to their duties and works and at the same time the organization or employer also fulfils all the needs of the employees. As a result, employees will have a high level of work satisfaction and the organization can enhance the company's performance. The theory of social cognitive career theory (SCCT) is suggested as a root of research study and the result of literature review also found that there are more potential factors influence the Work Satisfaction have to be study and expending of the role of Goal Direction Activity as a mediator in the theory. This concept paper is designed to assist researchers in conducting research on the level of work satisfaction among employees with special needs child and what factors influence it.